This can be worked out in a number of ways:
First way
1/(3+2i) = x+yi
So 1 = (3+2i)(x+yi) = 3x +3yi + 2ix -2y = (3x-2y) + i(3y+2x)
As 1 = 1+0i
1 + 0i = (3x-2y) + i(3y+2x)
So we have two simultaneous equations:
3x - 2y = 1 ............. (1)
2x + 3y = 0 ............. (2)
Multiply (1) by 3 and (2) by 2 then add
9x - 6y = 3 ............. (1)*3
4x + 6y = 0 ............. (2)*2
13x = 3
x = 3/13 and y = (3x-1)/2 = (9/13 - 1)/2 = -2/13
Checking answers:
3x - 2y = 3(3/13) - 2(-2/13) = 9/13 + 4/13 = 1
2x + 3y = 2(3/13) + 3(-2/13) = 6/13 - 6/13 = 0
So 1/(3+2i) = (3-2i)/13 = 3/13 - (2/13)i
Which is the same as (3+2i)*/||(3+2i)||² = (3-2i)/(3²+2²) = (3-2i)/13
Second way is to express (3+2i) in polar form
3+2i = r(cosφ + isinφ)
And 1/(3+2i) = (3+2i)ֿ¹ = rֿ¹(cosφ + isinφ)ֿ¹ = (cosφ + isinφ)ֿ¹/r²
And as (cosφ + isinφ)ֿ¹ = (cosφ - isinφ)
1/(3+2i) = (3+2i)ֿ¹ = (cosφ - isinφ)/||(3+2i)||²
1/(3+2i) = (3-2i)/13 = 3/13 - (2/13)i
2007-01-09 04:01:56
·
answer #1
·
answered by Andy 2
·
0⤊
0⤋
The reciprocal of 3 + 2i is...
(3-2i)/13 or (3/13) - (2i/13)
First you must rationalize the denominator by multiplying both the numerator and denominator by the conjugate of 3 + 2i. The conjugate of 3+ 2i is 3- 2i. multiplyin the numerators together you get 3 - 2i and multiplying the denominators together you get 9 - 4i^2. Since i^2 equals -1, the denominator changes to 9 + 4, which simplifies to 13. Therefore, the reciprocal of 3 + 2i is (3-2i)/13 OR (3/13) - (2i/13).
2007-01-09 02:43:31
·
answer #2
·
answered by coachandybrown 2
·
0⤊
0⤋
reciprocal is 1/(3+2i), but it is not in standard form
first of all try to rationalize the denominator by multiplying it with the conjugate i.e. 3-2i which gives u( 3-2i)/(3^2+2^2)
which finally gives u [(3/13)-i(2/13)] as the result
2007-01-09 02:45:48
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
The reciprocal of (3+2i) is (3+2i)*(3-2i)/(3-2i) which on simplifying gives (3/13)-(2/13)i.
2007-01-09 02:44:47
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
1/(3+2i) Multiply top and bottom by 3-2i
For the deonominator
(3+2i)(3-2i)=9-4i^2=9+4=13
So you get (3-2i)/13
In standard form divide the 13 into each term that is in the numerator
(3/13) + (-2/13) i
2007-01-09 02:44:55
·
answer #5
·
answered by Professor Maddie 4
·
0⤊
0⤋
1/(3 + 2i )
Conjugate of 3+2i = 3-2i
Multiply both numerator and denominator by conjugate of 3+2i
= (3-2i)/(3+2i)(3-2i)
= (3-2i)/(3*3 -3*2i + 3*2i -4*i²)
= (3-2i)/(9 - 4*(-1))
= (3-2i)/(9+4)
= (3-2i)/13
= (3/13) - (2/13)i
Thats in a + bi form you needed!
2007-01-09 02:41:39
·
answer #6
·
answered by Som™ 6
·
0⤊
0⤋
1/(3+2i) multiply top and bottom by 3-2i
1/(3+2i) (3-2i)/(3-2i) = (3-2i)/(9+4) = (3-2i)/13
= (3/13) + (-2/13) i .
2007-01-09 04:54:37
·
answer #7
·
answered by tablecloth 1
·
0⤊
0⤋
= 1/(3+2i)
= 1 * (3-2i)
------------
(3+2i) (3-2i)
= (3-2i)
-------------
(9 - 4i^2) i^2 = -1
= (3-2i) = (3-2i)
---------- ----------
9 - (-4) .. 13
2007-01-09 02:44:01
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
1/[3+2i]
=[3-2i]/[3+2i][3-2i]
=[3-2i]/[9+4]
=3/13-[2/13]i
=.23-.15i
2007-01-09 02:54:21
·
answer #9
·
answered by openpsychy 6
·
0⤊
0⤋